Social Connectedness and Online Design Learning Experience in the Indian Context - Vivek Gogu, Christy; Kumar, Jyoti (Design and Technology Education: An International Journal, 2021)
The rise in online courses and virtual learning avenues in the last few decades, and more recently the Covid-19 pandemic has seen traditional design schools imparting learning seamlessly by transitioning to the virtual realm partially or completely. This study helps understand the perspective of students from various design schools across India regarding their learning experience in online courses, virtual classrooms and their perceived social connectedness with peers and educators. We report findings from a mixed-methods study, which combined both quantitative and qualitative data collection and analysis, wherein ninety-five students from five design schools across India responded anonymously to the online questionnaire survey. We assessed the factors that impacted perceived social connectedness of the students with their educators and peers in online classes. We also discuss some of the reasons for this perception, as articulated by the participants, and report a significant correlation found between felt connectedness and various factors in online learning, such as visibility of participants, level of interaction during class, interest in course and understanding of the subject. It was observed that while the target student group seemed adept in online interaction and exchange of information, their feedback on online learning revealed unique insights into aspects that affect overall experience of design education. In addition, we submit some of the features or elements of traditional face-to-face (F2F) classrooms that students miss the most in the current online setting and some of the measures taken by students and educators to stay connected and overcome the virtual gap in learning.